Do Regions Benefit from Active Labour Market Policies? A Macroeconometric Evaluation Using Spatial Panel Methods. Issue 4 (2nd April 2016) - Dauth, Wolfgang; Hujer, Reinhard; Wolf, Katja
Abstract : Dauth W., Hujer R. and Wolf K. Do regions benefit from active labour market policies? A macroeconometric evaluation using spatial panel methods, Regional Studies . The effect of active labour market policies on all job seekers in a region is assessed using the variation in the participation in these programmes across regions over time. The starting point is an augmented regional matching function, which is extended by allowing for a heterogeneous search effectiveness parameter for current participants and job seekers who finished a measure recently. A spatial dynamic panel data model is estimated by using a quasi-ML estimation procedure. It is found that job schemes in the non-profit sector, wage subsidies and advancement of apprenticeships significantly increase the regional number of matches.